PERANCANGAN KAP LAMPU DEKORATIF BERBAHAN BIO LEATHER KACANG KEDELAI - Purwanto; Antonius Christanto Gunawan; Sekar Adita (Indonesian Society of Applied Science, 2022)
Soybean shell waste contains organic material with pH levels classified as acidic which can endanger environmental sustainability and pollute water and soil. This research raises the issue of utilizing soybean shell waste into more useful products. Soybean shell waste is used as new materials in the form of composites to be used as products that have economic value and overcome negative environmental impacts. The composite results in this study in this study were in the form of soybean skin bio leather sheets which were then analyzed for raw material talent to determine the potential of soybean skin bio leather sheets to be used as alternative product design materials. The actions taken to identify the talent of the sheet are by exploring and testing the translucency of the light to determine the distribution of the light produced, testing the sustainable sheet with the process of soaking the soil and water, and giving color. After analyzing material talent, in product design using the MACAK design method in the design so that product recommendations are found using soybean skin bio leather material. One of the product recommendations that can be developed is the design of a decorative lampshade with a Scandinavian concept with a weaving technique with a zig zag motif and geometry for hanging wall lamps, and table lamps using soybean skin bio leather. The results of the product design of hanging decorative lampshades, table lamps